Evaluating the risk of bacterial infections associated with the most handled Iraqi notes in Kalar - Tawfeeq, Hassan Mohammad; Fatah, Mohammed Hassan; Tofiq, Ahmed Mohammed (Kurdistan Journal of Applied Research, 2019)
Every day new sources of microbial and especially bacterial infections are reported, which are not taken into account, the fact that these sources have been implicated in the outbreaks of these infections. The goals of the current research focused on the exploration of the scope of microbial pollution of the widely traded paper currency notes of the Iraqi currencies (250, 1000 and 5000 Iraqi Dinars) in Kalar city. 300 banknotes (100 samples for each of the denominations under investigation) in circulation were gathered from different categories of Kalar population and one fresh sample for each of the three currencies (control negative). Each bill was rinsed in 5 ml D.W then cultured on Nutrient agar, Mannitol Salt agar and MacConkey agar, respectively, then incubated at 37 ºC for up to 48 hours. Results revealed the rate of microbial contamination, specifically bacterial ones as 94%, 68%, and 60%, respectively on the denominations of 250, 1000, and 5000 of Iraqi Dinars. In a descending order, and with regard to the prevalence rate, bacterial species contaminated 250, 1000 and 5000 Iraqi denominations respectively were as follows: 55.31%, 32.35% and 36.66% for Bacillus sp.; 14.89%, 38.23% and 20% for coagulase-negative Staphylococcus; 8.51%, 8.82% and 20% for E. coli; 2.12%, 11.76 and 20% for Pseudomonas sp.; 2.12% for each of Klebsiella sp., and Salmonella sp.; 10.63% and 4.25% for Enterobacter sp. and Staphylococcus aureus, respectively, and only on 250 denomination; 2.94% and 5.88% for each of Corynebacterium sp. and Serratia sp. only on 1000 currency note; lastly, 3.33% for Proteus sp. on 5000 IQD only. These outcomes suggest that bacterial contamination of Iraqi Dinars, specifically the 250 denomination is risky and could be regarded as the real source of infectious diseases with the most dangerous pathogenic bacteria.